The precise implementation of the ecological water transfer project effectively promotes the enhancement of desert riparian ecosystem service value in the mainstream of Tarim River - Ziwei Kang; Hongbo Ling; Yanming Gong; Junjie Yan; Feifei Han; Qianjuan Shan; Guangpeng Zhang (Ecological Indicators)
Ecosystem service value (ESV), as a crucial indicator concerning human and regional ecological well-being, has always been a hot topic in academia. Selecting appropriate assessment factors for arid areas to comprehensively explore the spatial–temporal heterogeneity of ESV and proposing pathways for ESV enhancement are currently challenging in research. This study incorporates three driving indicators, namely, human disturbance intensity (HDI), vegetation growth status (NIRv), and hydrological wetness condition (TVDI), into ESV calculation, efficiently improving the pixel-scale spatial heterogeneity manifestation of ESV. The study was conducted in a representative desert region of the Tarim River Basin (TRB), where ecological water transfer has effectively facilitated vegetation restoration. Based on this analysis, the total ESV in the TRB grew by 12.73 % between 2000 and 2022. Among them, ESVHDI, ESVNIRv, and ESVTVDI increased by 4.10 %, 58.25 %, and 18.78 % respectively. ESV in the four source rivers and mainstream of TRB increased by 4.36 % (YR), 60.77 % (TR), 2.94 % (AR), 3.88 % (HR), and 2.11 % (KR), with the ESV enhancement areas highly coinciding (coincidence degree is as high as 60.64 % of the mainstream of TRB) with the Populus euphratica forest water transfer area. ESV in the ecological water transfer area increased by 51.27 %, especially in the mainstream of the TRB water transfer area, where ESV increased by 62.32 %. Based on the perspectives of water use benefit (ESV/ET) and efficiency (ET/NIRv), to improve the ecological water use efficiency and ESV even further, the water supply thresholds of forests, grasslands, and wetlands should be controlled within the ranges of [495.37 mm–553.45 mm], [474.25 mm–528 mm], and [1011.68 mm–1070.64 mm], respectively. This study not only provides new insights for ESV calculation in arid areas but also offers scientific guidance for precise management of arid ecosystem.